Interrelationships of emotional intelligence with the awareness of request and apology strategies in an EFL setting - Ghenaati, Zohreh; Naeini, Ma’ssoumeh Bemani (Universitas Pendidikan Indonesia, 2019)
Taking the approach of interlanguage pragmatic analysis based on the theories of Speech Acts and Emotional Intelligence (EI), the main purpose of the present study was to find the interrelationships among components of EI, and awareness of request and apology strategies among Iranian TEFL students. The study was conducted on 200 English teaching majors from Mashhad universities. EI was measured through a translated form of Bar-On emotional quotient inventory and a self-developed questionnaire for measuring the apology and request strategies. The results of path analysis showed that among five sub-constructs of EI, four variables positively and significantly predict request strategies: Interpersonal (β= .40, p.05), Intrapersonal (β= .16, p.05), Adaptability (β= .17, p.05), and Stress management (β= .15, p.05). Moreover, among five sub-constructs of EI, three variables of Interpersonal (β= .16, p.05), Intrapersonal (β= .22, p.05), and Stress management (β= .12, p.05) are predictors of apology strategy. The results also indicate that the proposed model had a perfect fit with the empirical data. Furthermore, the results of correlation showed that General Mood is positively and significantly correlated with apology and request. Thus, it is suggested that educators and policymakers consider the importance of EI in improving request and apology strategies.